Diversity of weeds species in grapes farms of Tayma (Tabuk, Saudi Arabia): implication for invasive species ecology (Bioscience Journal, 2023)
The biodiversity of the agroecosystem leads to changes in the Floristic composition, diversity, and abundance of weed species in crop and orchard farms. The present study is considered the first attempt to categorize, evaluate, and document the diversity of weed populations among different grape farms in Tayma, Tabuk region, Saudi Arabia. The results of ANOVA showed that the number of weed species varied significantly across the six grape farms. During six grape farms under study, 30 weed species belonging to thirteen families and 28 genera were recorded. In total, twelve weed species belong to the Poaceae family with a rate of 40%. While the other families are represented either by one or two species with rates of 3.3% and 6.7%, respectively. Biogeographic origins analysis showed that the Tropical area represented 23.3% of total weed flora, followed by Saharo Arabian (16.7%), Mediterannean-Euro Siberian-Irano-Turanian (13.3%) and American (10.0%). Therophytes were the dominant life forms with a rate of 66.7%, followed by Hemicryptophyte (20.0%), Geophyte (6.7%), and Chamaephyte (6.7%). A total of 16 and 14 weed species belong to the annual and perennial life span, respectively. Also, the grass and herb habits represented 40% and 60% of 30 weed species, respectively. According to the abundance score, the most common weed species of those grape farms in the region study are Cynodon dactylon, Desmostachya bipinnata, and Setaria verticillata, they belong to the Poaceae family. Based on the presence and absence of weed species in grape farms, the Principal Component Analyses (PCA) show that the grape farms and weed species (into two groups) are distinguished mainly along the first two components. Also, positive correlations were observed among most grape farms, according to PCA. Generally, more studies on the ecological aspects and floristic composition of weed species in grape farms are also needed.